Effectiveness of Village Health Worker–Delivered Smoking Cessation Counseling in Vietnam. Issue 11 (29th October 2018) - Jiang, Nan; Siman, Nina; Cleland, Charles M; Van Devanter, Nancy; Nguyen, Trang; Nguyen, Nam; Shelley, Donna
Abstract: Introduction: Smoking prevalence is high in Vietnam, yet tobacco dependence treatment (TDT) is not widely available. Methods: We conducted a quasiexperimental study that compared the effectiveness of health care provider advice and assistance (ARM 1) versus ARM 1 plus village health worker (VHW) counseling (ARM 2) on abstinence at 6-month follow-up. This study was embedded in a larger two-arm cluster randomized controlled trial conducted in 26 community health centers (CHCs) in Vietnam. Subjects ( N = 1318) were adult patients who visited any participating CHC during the parent randomized controlled trial intervention period and were self-identified as current tobacco users (cigarettes and/or water pipe). Results: At 6-month follow-up, abstinences rates in ARM 2 were significantly higher than those in ARM 1 (25.7% vs. 10.5%; p < .001). In multivariate analyses, smokers in ARM 2 were almost three times more likely to quit compared with those in ARM 1 (adjusted odds ratio [AOR] = 2.96, 95% confidence interval [CI] = 1.78% to 4.92%). Compared to cigarette-only smokers, water pipe–only smokers (AOR = 0.4, 95% CI = 0.26% to 0.62%) and dual users (AOR = 0.62, 95% CI = 0.45% to 0.86%) were less likely to achieve abstinence; however, the addition of VHW counseling (ARM 2) was associated with higher quit rates compared with ARM 1 alone for all smoker types. Conclusion: A team approach in TDT programs that offer a referral system for health care providers to refer smokers to VHW-led cessation counseling is a promising and potentially scalable model for increasing access to evidence-based TDT and increasing quit rates in low middle-income countries (LMICs). TDT programs may need to adapt interventions to improve outcomes for water pipe users. Implications: The study fills literature gaps on effective models for TDT in LMICs. The addition of VHW-led cessation counseling, available through a referral from primary care providers in CHCs in Vietnam, to health care provider's brief cessation advice, increased 6-month biochemically validated abstinence rates compared to provider advice alone. The study also demonstrated the potential effectiveness of VHW counseling on reducing water pipe use. For LMICs, TDT programs in primary care settings with a referral system to VHW-led cessation counseling might be a promising and potentially scalable model for increasing access to evidence-based treatment.